JARANAN TURONGGO SEKTI: TINJAUAN ETNOGRAFI ANALITIS DARI SUDUT PANDANG UNSUR-UNSUR KEBUDAYAAN - Afif Widyanto (BBPPMPV Seni dan Budaya Yogyakarta, 2023)
The purpose of the current study is to describe the existence of Jaranan Turonggo Sekti as an art productin Suruh Village Trenggalek which is reviewed from the analytical ethnography with the approach ofelements of culture. The underlying concept of Koentjaraningrat’s ethnography framework (2015) wasemployed, stating that there are seven elements of culture, namely (1) religion and religious ceremonies,(2) system of social organization, (3) knowledge system. (4) language. (5) arts, (6) economic system andlivelihood, and (7) living equipment and technology system. In traditional culture, seven elements of cultureare closely linked, integrated one of another, forming part of a whole system. The results of the studydemonstrate that Jaranan Turonggo Sekti describes religion or belief system and religious ceremoniesthrough the rituals of offerings and sense-making of the braid horse being used. System of socialorganization or social relations are portrayed through the spirit of the community, while local knowledgeis applied in the creation of horse figure and its decoration. Language is represented in the form of visuallanguage, whereas arts element, particularly fine arts elements is signified by the figure of the horse.Livelihood system is interpreted in a simple economic concept in which the performance is held with paidresponse model. Technology element is carried out through the process of braid horse making determinedby the technical ability of the person who creates it.